Thinking Europe from the margins and through marginal cinema: The case of The Nothing Factory (Pinho, 2017). (1st January 2020) - Liz, Mariana
AbstractA Fábrica de Nada (The Nothing Factory) (Pinho, 2017) tells the story of a group of workers struggling to keep their jobs at a lift factory in Portugal about to be relocated. Awarded the FIPRESCI prize at the 2017 edition of the Cannes Film Festival, the film was received by critics as a 'compelling oddity', an 'enigmatic epic' and 'something genuinely new in cinema'. Almost three hours in length, and a mix of fiction and documentary, drama and musical, The Nothing Factory rehearses, also through its style and production history, the uncertainty that characterizes contemporary European society. As it depicts austerity in Portugal through a post-national lens, what does The Nothing Factory tell us about European identity? This article examines the contradictions of globalization and neo-liberalism, in tandem with the difficulties in sustaining narratives and creating meaning in contemporary European film. The Nothing Factory is a prime example of the cinema of small nations currently produced in Portugal, and a consideration of marginal and peripheral cinemas such as this one is crucial for the understanding of what is left of European identity, in geographical, political and cultural terms.